We, singular plural (fragments of a conversation) - Silva, Rodrigo Rebelo (Farol, 2025)
This philosophical essay examines the problematic nature of the pronoun "We" as a contested political and ontological concept. Drawing on Jean-Luc Nancy’s notion of "singular plural," the text critiques fixed collective identities (national, ethnic, or ideological) as reductive and exclusionary. It explores the tension between the need for community articulation for political agency and the risks of homogenization, highlighting how "We" oscillates between emancipatory potential and coercive appropriation. Contemporary thinkers such as Judith Butler, Tristan Garcia, and ecological theorists (e.g., Baptiste Morizot) inform discussions of fluid collectives, intersectionality, and nonhuman alliances. The author advocates for "We" as an open and procedural practice—anchored in shared action, not identity—to navigate fragmented public spheres, ecological interdependence, and ethical responsibility in the face of polarization.